2017
DOI: 10.1590/s0100-204x2017001000011
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum species and activity in sandy soil solution with pig slurry addition

Abstract: -The objective of this work was to evaluate the effect of pig slurry applications on the exchangeable Al content, activity, and distribution of Al chemical species in the soil solution. Soil samples of a Typic Hapludalf were obtained from an experiment conducted during eight years, with 19 applications of 0, 20, 40, and 80 m 3 ha -1 pig slurry. The soil samples were collected in stratified layers to determine exchangeable Al content and to extract the soil solution by the saturated soil paste method. The conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
(34 reference statements)
2
5
0
1
Order By: Relevance
“…In field conditions, Nolla et al (2013) also observed the formation of Al phosphate by the release of organic acids by soybean plants that are able to complex the Al in the soil solution under conditions of higher acidity. De Conti et al (2017) applied increasing doses of swine manure and also verified the increase of the formation of Al complexed with P due to the increase of the concentration of this element in solution, mainly in the upper layers of the soil evaluated in this study. Zambrosi et al (2008) evaluated the distribution of Al and nutrient species in the solution in a dystrophic Red Latosol after five years of limestone application and also identified the presence of the complex formed between Al and phosphate in the upper layers and concluded that the phosphate ions in the solution are prone to strong interactions with Al, Fe, Ca and Mg.…”
Section: Anions In Solutionsupporting
confidence: 70%
See 4 more Smart Citations
“…In field conditions, Nolla et al (2013) also observed the formation of Al phosphate by the release of organic acids by soybean plants that are able to complex the Al in the soil solution under conditions of higher acidity. De Conti et al (2017) applied increasing doses of swine manure and also verified the increase of the formation of Al complexed with P due to the increase of the concentration of this element in solution, mainly in the upper layers of the soil evaluated in this study. Zambrosi et al (2008) evaluated the distribution of Al and nutrient species in the solution in a dystrophic Red Latosol after five years of limestone application and also identified the presence of the complex formed between Al and phosphate in the upper layers and concluded that the phosphate ions in the solution are prone to strong interactions with Al, Fe, Ca and Mg.…”
Section: Anions In Solutionsupporting
confidence: 70%
“…This may have occurred because these soils have a high concentration of Al in the solution and the addition of P increases the concentration of phosphate ions (Table 2), favoring the formation of Al-HPO 4 + , (55% in PE and 59% in BR of the total phosphate ions in the solution). The strong interaction of these ions with Al, Fe and Mn is well known and results in decreased availability of P in the solution and also reduced risk of Al toxicity to plants (Rutkowska et al, 2015;De Conti et al, 2017). In a lower proportion, HPO 4 2was found in the same treatments, 0.33% in AC9, 0.12% in PE, 0.75% in RS, 0.2 in BR and 0.3% in CB.…”
Section: Anions In Solutionmentioning
confidence: 94%
See 3 more Smart Citations